Hepatocyte-specific deletion of Pparα promotes NAFLD in the context of obesity - Régnier, Marion (Sci Rep, 2020)
Peroxisome proliferator activated receptor α (PPARα) acts as a fatty acid sensor to orchestrate the transcription of genes coding for rate-limiting enzymes required for lipid oxidation in hepatocytes. Mice only lacking Pparα in hepatocytes spontaneously develop steatosis without obesity in aging. Steatosis can develop into non alcoholic steatohepatitis (NASH), which may progress to irreversible damage, such as fibrosis and hepatocarcinoma. While NASH appears as a major public health concern worldwide, it remains an unmet medical need. In the current study, we investigated the role of hepatocyte PPARα in a preclinical model of steatosis. For this, we used High Fat Diet (HFD) feeding as a model of obesity in C57BL/6 J male Wild-Type mice (WT), in whole-body Pparα(-) deficient mice (Pparα(−/−)) and in mice lacking Pparα only in hepatocytes (Pparα(hep−/−)). We provide evidence that Pparα deletion in hepatocytes promotes NAFLD and liver inflammation in mice fed a HFD. This enhanced NAFLD susceptibility occurs without development of glucose intolerance. Moreover, our data reveal that non-hepatocytic PPARα activity predominantly contributes to the metabolic response to HFD. Taken together, our data support hepatocyte PPARα as being essential to the prevention of NAFLD and that extra-hepatocyte PPARα activity contributes to whole-body lipid homeostasis.